Identification of rickettsial immunoreactive proteins using a proximity ligation assay Western blotting and the traditional immunoproteomic approach. (June 2018) - Kowalczewska, Malgorzata; N'Djatchi, Aymar; Nappez, Claude; Alwassouf, Sulaf; Decloquement, Philippe; Armstrong, Nicholas; El Karkouri, Khalid; Edouard, Sophie; Raoult, Didier
Graphical abstract: Highlights: Two proteomics- based techniques are used for screening R. africae and R. conorii new diagnostic protein targets. New technique named in situ proximity ligation assay in 2-D Western blotting has been developed. Both approaches were compared and evaluated. Several rickettsial proteins with diagnostic potential were identified. They may be proposed for developement of rickettsial serodiagnosis. Abstract: The closely related species Rickettsia conorii and R. africae are both etiological agents of rickettsiosis, a tick-borne serious infective disease. The laboratory diagnosis is based on serology, but remains not enough specific to provide the diagnosis at the species level. Here, we attempted to identify specific proteins that would enable the discrimination of R. africae sp from R. conorii sp infections. We screened 22 R. africae - and 24 R. conorii -infected sera at different course of infection using a traditional immunoproteomic approach. In parallel, we focused on the technical development of a "relatively new technique" named a proximity ligation assay coupled to two-dimensional Western blotting. The top range markers of R. africae early infection were rpoA, atpD, and acnA, ORF0029, R. africae active infection were rOmpB β-peptide, OmpA, groEL and ORF1174, early R. conorii infection was prsA, RC0031, pepA, R. conorii active infection were ftsZ, cycM and rpoA. They are candidates for serodiagnosis of rickettsioses.